Mixed-integer programming models for optimal constellation scheduling given cloud cover uncertainty - Valicka, Christopher G.; Garcia, Deanna; Staid, Andrea; Watson, Jean-Paul; Hackebeil, Gabriel; Rathinam, Sivakumar; Ntaimo, Lewis (European journal of operational research, 2019)
•We propose a simple and improved mixed-integer programming sensor scheduling model.•Stochastic variants proactively schedule against weighted cloud-cover scenarios.•Schedule utility is improved, using commercial solvers, over deterministic models.•Schedules resilient to uncertain weather are produced within operational run times. We consider the problem of scheduling observations on a constellation of remote sensors, to maximize the aggregate quality of the collections obtained. While automated tools exist to schedule remote sensors, they are often based on heuristic scheduling techniques, which typically fail to provide bounds on the quality of the resultant schedules. To address this issue, we first introduce a novel deterministic mixed-integer programming (MIP) model for scheduling a constellation of one to n satellites, which relies on extensive pre-computations associated with orbital propagators and sensor collection simulators to mitigate model size and complexity. Our MIP model captures realistic and complex constellation-target geometries, with solutions providing optimality guarantees. We then extend our base deterministic MIP model to obtain two-stage and three-stage stochastic MIP models that proactively schedule to maximize expected collection quality across a set of scenarios representing cloud cover uncertainty. Our experimental results on instances of one and two satellites demonstrate that our stochastic MIP models yield significantly improved collection quality relative to our base deterministic MIP model. We further demonstrate that commercial off-the-shelf MIP solvers can produce provably optimal or near-optimal schedules from these models in time frames suitable for sensor operations.